Situational and analytical centers of the Internal Affairs Department - the guarantee of effective management of power tools (Eurasian Research Bulletin, 2024)
In this article, the author describes the situational analysis of the Ministry of Internal Affairs, which was organized in accordance with the decision of the President of the Republic of Uzbekistan "On further improvement of the activities of ensuring public safety and combating crime with the wide introduction of achievements in the field of modern digital technologies" dated September 22, 2022 PQ No. 379 explained the main tasks and functions of the center.